More Light? Opportunities and Pitfalls in Digitalized Psychotherapy Process Research - Domhardt, Matthias; Cuijpers, Pim; Ebert, David Daniel; Baumeister, Harald (Frontiers in Psychology, 2021)
While the evidence on the effectiveness of different psychotherapies is often strong, it is not settled whereby and how these therapies work. Knowledge on the causal factors and change mechanisms is of high clinical and public relevance, as it contributes to the empirically informed advancement of psychotherapeutic interventions. Hereby, digitalised research approaches might possess the potential to generate new insights into human behaviour change, contributing to augmented interventions and mental healthcare practices with better treatment outcomes. In this perspective article, we describe recent findings of research into change mechanisms that were only feasible with digital tools, and outline important future directions for this rather novel branch of research. Furthermore, we indicate several challenges and pitfalls that are to be solved, in order to advance digitalised psychotherapy process research, both methodologically and technologically.